Pelatihan Pembuatan Blog / Website Pribadi Gratis Untuk Siswa Di SMPN 4 Tangerang Selatan - Indra Kristianto; Ahmad; Muhammad Santoso (AMMA : Jurnal Pengabdian Masyarakat, 2023)
A blog / website is an online journal or journal that contains a variety of information, such as articles, photos or videos, which are updated regularly. PKM activities at the Tangsel 4 Middle School in the South Tangerang area this time we will provide training on creating personal blogs/websites for free with the aim of students knowing how to create them from the start. Apart from that, creating a blog can be useful for improving oneself both in iincreasing knowledge and improving writing skills and the ability to understand technology.